“MI AYAM ORA KUDU ANA AYAME”: PEMAKAIAN BAHASA DALAM WACANA HUMOR BOCAH NGAPA(K) YA, PELANGGARAN PRINSIP KERJA SAMA, DAN RELASI HUMORNYA - Ridha Mashudi Wibowo (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
In addition to serving as a medium of daily communication, the Banyumas dialect can also be used for entertainment, as seen in the television program Bocah Ngapa(k) Ya. This article seeks to identify linguistic quirks and pragmatic maxims that have the potential to be humorous. The data was collected from gathered information through the episode transcripts of the Bocah Ngapa(k) Ya video series, which were downloaded using YouTube Trans7 using the download-transcript-listen-record procedure from April to June 2019. The finding transcriptions were then described utilizing comparison, introspection, and pragmatic equivalent techniques. What linguistic components are crucial for producing the humour effect? How does the principle work? These are questions that the analysis is trying to address.